COMPARISON OF FUNCTIONAL MOVEMENT SCREENING (FMS) SCORE IN FUTSAL PLAYERS. Issue 7 (11th March 2014) - Mendes de Almeida Gomide Leite, M; Bolling, C; Reis, D
Abstract : Background: The FMS (Functional Movement Screening) is a functional assessment based on mobility and stability and mechanical factors which contributes to develop injury prevention programs. Objective: To compare FMS score between different categories in futsal athletes. Design: This is a cross sectional, retrospective study using FMS assessment method. Setting: This study was conducted with national level futsal players, during preseason in a Brazilian sports club. Participants: 37 male athletes were evaluated, 16 athletes from under 20 years category, with a mean age of 19.28 years (±1.34), mean weight of 71.52 kg (±6.70), average height of 181.61 cm (±9.82 ) and 21 athletes of professional category, with a mean age of 20.93 years (±4.44), mean weight of 77.35 kg (±11.61) and average height of 174.93 cm (±6.51). Interventions: All the athletes were evaluated by a physiotherapist experienced in FMS method. Each test was performed once to record the score of the athlete. Main outcome measurements: 7 tests (deep squat, hurdle step, in-line lunge, shoulder mobility, active straight leg raise, trunk stability push up, rotational stability) were performed. The scores were compared by student's t-test, using SPSS software. Results: The mean score of under 20 category was 15 (±1.75) and 15.90 (±1.86) for professional. Comparative analysis between categories showed no significant difference (P<.05 ). Conclusion: The similarity in training and competition demands could explain the absence of difference in functional measurements between under 20 and professional athletes. Many under 20 players are part of professional team, so prevention strategies in under 20 need to prepare the youth athletes to professional carrer.